2014
DOI: 10.4317/medoral.19477
|View full text |Cite
|
Sign up to set email alerts
|

Influence of occlusal loading on peri-implant clinical parameters. A pilot study

Abstract: Objectives: To investigate the relation between occlusal loading and peri-implant clinical parameters (probing depth, bleeding on probing, gingival retraction, width of keratinized mucosa, and crevicular fluid volume) in patients with implant-supported complete fixed prostheses in both arches. Material and Methods: This clinical study took place at the University of Valencia (Spain) dental clinic. It included patients attending the clinic for regular check-ups during at least 12 months after rehabilitation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…Other studies (Heitz-Mayfield et al, 2004;Kozlovsky et al, 2007) have observed that excessive occlusal loading was created in the antagonist arch using one-piece crowns (Pellicer-Chover et al, 2014).…”
Section: Sanzmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies (Heitz-Mayfield et al, 2004;Kozlovsky et al, 2007) have observed that excessive occlusal loading was created in the antagonist arch using one-piece crowns (Pellicer-Chover et al, 2014).…”
Section: Sanzmentioning
confidence: 99%
“…In this review, no definitive conclusion could be established in terms of the most effective loading method (Cannizzaro et al, 2010;Margossian et al, 2012;Sanz-Sánchez et al, 2014;Vogl et al, 2013). Pellicer-Chover et al (2014) investigated the relationship between occlusal loading and peri-implant clinical parameters (probing depth, bleeding on probing, gingival retraction, width of keratinised mucosa, and crevicular fluid volume) in patients with implant-supported complete fixed prostheses in both arches. They concluded that the maxillary implant closest to the point of highest occlusal loading presented significantly higher volumes of crevicular fluid compared to the maxillary implant with the least loading that was furthest from the study implant.…”
Section: Implant and Abutment Designmentioning
confidence: 99%
“…So the occlusal adjustment was performed at a subclinical level (the patient did not feel any difference after the adjustment). The analysis of the changes in the cytokine expression is a subclinical parameter and is a complementary analysis to the changes in the PICF volume that we published before [ 13 ]. This subclinical level (there is no pathology) might be the reason why, before occlusal adjustment, some cytokines are highly expressed in the test implants while some others presented higher values in the control implants.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous human study [ 13 ], our group found that implants receiving higher occlusal loading presented significantly higher PICF volumes than implants with less occlusal loading. Two and 12 months after occlusal adjustment, PICF volumes were similar in both groups.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation